Political Dynasties, Business, and Poverty in the Philippines - Mendoza, Ronald U (Archīum Ateneo, 2022)
Despite studies finding a link between political dynasty prevalence and poverty; empirical evidence in the Philippines shows that the relationship between dynastic concentration and underdevelopment is not the same across regions. We argue that an independent economic elite and high levels of economic activity; typically found in Luzon; affect the poverty and development impact of political dynasties. Local socioeconomic contexts shape the opportunities for predatory behavior among politicians and their relationships with economic elites. Using novel survey data on business-government linkages as well as an extensive dataset on local government leadership in the Philippines spanning 2004 to 2016; we find that political dynasties exacerbate poverty in the resource-rich non-Luzon provinces but not in Luzon where there is a competitive business environment.